Robert D. Attenborough & Michael P. Alpers (eds.): Human Biology in Pagua New Guinea. The Small Cosmos - Wolff, Bente (Tidsskriftet Antropologi, 2019)
Robert D. Attenborough & Michael P. Alpers (eds.): Human Biology in Pagua New Guinea. The Small Cosmos Anmeldes af Bente Wolff